Isochromanes from Aspergillus fumigatus, an endophytic fungus from Cordyceps sinensis. Issue 13 (3rd July 2019) - Li, Xiao-Hua; Han, Xue-Hua; Qin, Ling-Ling; He, Jun-Lin; Cao, Zhi-Xing; Gu, Yu-Cheng; Guo, Da-Le; Deng, Yun
Abstract: Four previously undescribed isochromanes were isolated from the fermentation broth of an endophytic fungus Aspergillus fumigatus, which was obtained from the fruiting body of Cordyceps sinensis . Their structures were elucidated through extensive spectroscopic analyses. One racemic isochromane was further purified by chiral HPLC to yield a pair of enantiomers and their absolute configurations were determined by quantum chemical ECD calculations. These isolated compounds were evaluated for cytotoxicity against two cell lines (MV4-11 and MDA-ME-231) and the result showed that compounds1a and2 exhibited moderate growth inhibition against MV4-11 cell line. Abstract :